Impact of root canal treatment on high‐sensitivity C‐reactive protein levels in systemically healthy adults with apical periodontitis – a preliminary prospective, longitudinal interventional study. (11th December 2020) - Poornima, L.; Ravishankar, P.; Abbott, P. V.; Subbiya, A.; PradeepKumar, A. R.
Abstract: Aim: To assess the influence of root canal treatment on serum high‐sensitivity C‐reactive protein (hsCRP) levels in systemically healthy human adults. Methodology: Fifteen individuals aged 20–40 years diagnosed with apical periodontitis [Periapical Index (PAI) score ≥3] who were otherwise healthy took part in this prospective interventional study. Patients with moderate to severe periodontitis, systemic diseases and traditional cardiac risk factors (hypertension, diabetes, dyslipidemia and smoking) were excluded. Root canal treatment was completed in two visits with an inter‐appointment calcium hydroxide intracanal medicament. After 6 months, healing of apical periodontitis was evaluated clinically and radiographically, and serum hsCRP levels were recorded. A paired sample T ‐test was used to compare the mean hsCRP values between the pre‐ and post‐treatment groups. The Mann–Whitney U test was used to compare hsCRP values between patients with PAI scores of 3 and 4, and the Wilcoxon signed‐rank test was used to compare pre‐ and postoperative PAI scores. Results: The mean preoperative baseline serum hsCRP level was 2.88 ± 1.06 mg L −1 which can be associated with a moderate risk for cardiovascular disease (CVD). Based on the preoperative hsCRP levels, eight of the 15 patients were categorized as high risk (hsCRP > 3 mg L −1 ) and the other seven as medium risk (hsCRP 1–3 mg L −1 ) for CVD. The mean preoperative hsCRP value of patients with a PAI score of 3 was 2.88 ± 1.19 mg L −1, and the mean preoperative hsCRP of patients with a PAI score of 4 was 2.87 ± 0.15 mg L −1, which was not significantly different ( P = 0.942). Six months after root canal treatment, the mean PAI score had significantly reduced from 3.2 ± 0.42 to 1.4 ± 0.69 ( P = 0.003). The PAI score had reduced to ≤2 in 87% of the patients, and the mean serum hsCRP levels had significantly reduced to 1.34 ± 0.52 mg L −1 ( P < 0.001). Ten of the 15 patients had a reduction in their CVD risk status. Conclusions: This study suggests that root canal treatment can reduce serum hsCRP levels in systemically healthy individuals with apical periodontitis.